A Success Case Method Evaluation of An Executive Coach Training Intervention - Beets, Karolyne Elizabeth (Institute for Monitoring and Evaluation, 2024)
This evaluation examines the extent to which 2005 and 2006 Associate Coaching Course participants have successfully applied the proximal outcomes from the executive coach training. Following the Success Case Method, a survey determined that the majority of participants rated their application of the learnings very successfully. A qualitative data analysis of eight interviews conducted with six high success cases (three professional coaches and three within-job coaches) and two low success cases, explored their application of the proximal outcomes in detail. The results report on various themes that describe how the coaches have applied the training, what results they have achieved and what value has come from the training. Further themes address factors that helped or hindered application and suggestions for training improvement. It can be concluded that the Associate Coaching Course was successful for this group of participants in that they report successful on-the-job application of the proximal outcomes and provide examples of positive results achieved due to this application. Furthermore, this evaluation contributes to a relatively scant literature concerning the application of the Success Case Method of evaluation.